Applications of business intelligence and marketing analytics in the complementary and alternative medicine industry. Issue 1 (May 2021) - Kanchanapoom, Kessara; Chongwatpol, Jongsawas
This case is designed to illustrate the application of business intelligence and marketing analytics to making proper decisions in a competitor-oriented pricing environment. The case started when Dan, the director of a business analytics consulting firm, was assigned a big project: to help Panacée Medical Center, one of the leading service providers in complementary and alternative medicine industry, envisage possible marketing strategies in response to competitors' recent moves that threatened the sales and marketing strategies of its business. The case is divided into three parts. Case A provided an overview of challenges Panacée was facing when one of its competitors, Beauty and Clinic, was about to offer full complementary and alternative medicine services with a newly renovated, 5-star, resort-type clinic and high-quality facilities and another competitor, Natural Health Center, planned to promote its recent investment in a new laboratory that met international standards at the upcoming Thailand Health & Wellness Expo. Case B focused on insights into customers through different analytical techniques. Case C implicitly outlined possible strategies that might be applicable to Panacée, especially when the services from both Beauty and Clinic and Natural Health Center were expected to be priced 5% to 25% below the established market price. Dan needed to decide which direction he needed to propose to Panacée's top management, as the combination of low prices and premium services threatened the medical center and Panacée might lose as much as 30% of its forecast revenue next year.